Experimental and numerical investigations on a novel plate anchorage system to solve FRP debonding problem in the strengthened RC beams. (January 2022) - Esmaeili, Jamshid; Aghdam, Orang Ranjbar; Andalibi, Keyvan; Kasaei, Jamil; Gencel, Osman
Abstract: Method of externally bonded reinforcement (EBR) is one of the most prominent systems for retrofitting reinforced concrete (RC) beams containing fiber-reinforced polymers (FRP). Many studies conducted in this field confirm the fact that the majority of the beams strengthened in this way experience failure due to the sudden detachment of FRP sheets from the concrete substrate. In this regard, an innovative plate anchorage technique was presented to solve the FRP debonding problem. In this method (EBR by Welded Steel Plates), two plates are placed near the beam supports, which are connected by welding to a longitudinal tension reinforcement through the angles. FRP sheets are placed on seat plates at both ends and fixed in their position by another plate placed over them. Ten RC beams with 150 × 200 × 2000 mm were prepared from concrete in 21 and 35 MPa strength classes. All specimens were subjected to a quasi-static four-point bending test. A comparative study was also done using an analytical method and comparing experimental results in the literature. This research results revealed that the better and more practical performance of the suggested plate anchorage system resulted in postponing or completely solving the FRP surface debonding problem. Highlights: A new type of plate anchorage system was developed to solve FRP debonding problem. Failure mechanism in all plate anchored beams manifested as the rupture of anchored FRP sheets. An increase in Pu, Δpu and then energy absorption was observed in all plate anchored strengthened beams. Results revealed the better and more practical performance of the suggested plate anchorage system.